Cyclic tests on steel and concrete-filled tube frames with Slit Walls. - Hitaka, Toko (Earthquake engineering & structural dynamics.)
Cyclic loading tests were performed on three one-storey steel frames and four three-storey concrete-filled tube (CFT) moment frames reinforced with a new type of earthquake-resisting element consisting of a steel plate shear wall with vertical slits. In this shear wall system, the steel plate segments between the slits behave as a series of flexural links, which provide fairly ductile response without the need for heavy stiffening of the wall. The steel shear walls and the moment frames behaved in a ductile manner up to more than 4% drift without abrupt strength degradation or loss of axial resistance. Results of these tests and complementary analysis provide a basis for an equivalent brace model to be employed in commercially available frame analysis programs. Test and analytical results suggest that the horizontal force is carried by the bolts in the middle portion of the wall?frame connection, while the vertical forces coupled with the moment in the connection are resisted by the bolts in the edge portion of the connection, for which the friction bolts in the connection should be designed. When sufficient transverse stiffening is provided, full plastic strength and non-degrading hysteretic behaviour can be achieved for this new type of shear wall.